THE PARENTING POCKETBOOK AS A MEANS OF STIMULATING CHILDREN'S EXPRESSIVE LANGUAGE: A STUDY ON THE DEVELOPMENT OF THE ADDIE MODEL - Yeni Heryani; Erna Budiarti (Adisam Publisher, 2026)
This research aims to develop a parenting pocket book media to enhance the expressive language skills of children aged 5-6 years at TKN Pasar Rebo 04. The research method used is research and development (R&D) with a qualitative and quantitative (mixed methods) approach based on the ADDIE development model. The process of developing this parenting pocket book involves several stages, starting from needs analysis, design, prototype creation, to limited trials. Data is collected through observations and interviews conducted with teachers, parents, and children at TKN Pasar Rebo 04. The research results indicate that the parenting pocket book media is proven to be suitable for use based on the validation results from experts, with an average total validation score of 78.63% (suitable category). The aspect of language suitability for children received the highest score with an average of 81.00% (very suitable), followed by the suitability aspect for practitioners at 80.00% (suitable), media suitability at 78.00% (suitable), and the suitability of early childhood education materials at 75.50% (suitable). Overall, the evaluation results indicate that this parenting pocketbook is very effective in providing clear and easy-to-follow guidance for parents to enhance their children's expressive language skills